Effects of exercise on the isoelectric patterns of erythropoietin - Lamon, S.; Martin, L.; Robinson, N.; Saugy, M.; de Ceaurriz, J.; Lasne, F. (Clinical Journal of Sport Medicine, 2009)
Objectives: Recombinant erythropoietin has a strong impact on aerobic power and is therefore one of the most potent doping agents in endurance sports. The anti-doping control of this synthetic hormone relies on the detection, in the urine, of its isoelectric pattern, which differs from that of the corresponding natural hormone, the latter being typically more acidic than the former. However, a small number of natural urinary patterns, referred to as "atypical patterns," are less acidic than the dominant form. Based on anecdotal evidence, the occurrence of such patterns seems to be related to particular strenuous exercises. This study aimed to demonstrate this relation using a strenuous exercise protocol.